2008
DOI: 10.1002/jobm.200700291
|View full text |Cite
|
Sign up to set email alerts
|

Removal of chromium (VI) through biosorption by the Pseudomonas spp. isolated from tannery effluent

Abstract: Heavy metal contamination of the rivers is a world wide environmental problem and its removal is a great challenge. Kanpur and Unnao two closely located districts of Uttar Pradesh India are known for their leather industries. The tanneries release their treated effluent in the near by water ways containing Cr metal that eventually merges with the river Ganges. Untreated tannery effluent contains 2.673 +/- 0.32 to 3.268 +/- 0.73 mg l(-1) Cr. Microbes were isolated, keeping the natural selection in the view, fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The Conventional methods used for the removal of heavy metals in contaminated effluent includes electrochemical treatment, ion exchange, evaporation, chemical precipitation, reverse osmosis, and sorption, however all these physical and chemical methods were observed to have technical and economical constrains like high cost of operation and release of chemical and huge sludge to the environment as by-product therefore the need to replace them with cost effective and environmental friendly biological method of treatments [17].…”
Section: Introductionmentioning
confidence: 99%
“…The Conventional methods used for the removal of heavy metals in contaminated effluent includes electrochemical treatment, ion exchange, evaporation, chemical precipitation, reverse osmosis, and sorption, however all these physical and chemical methods were observed to have technical and economical constrains like high cost of operation and release of chemical and huge sludge to the environment as by-product therefore the need to replace them with cost effective and environmental friendly biological method of treatments [17].…”
Section: Introductionmentioning
confidence: 99%
“…Data in literature about metal-microbe interactions, metal sorption and metal desorption processes from bacteria (Srivastava et al, 2008) show that positively charged metal ions are sequestered primarily through the adsorption of metals to the negative ionic groups on cell surfaces, the polysaccharide coating present in most forms of bacteria or other extracellular structures, such as capsules or slime layers. The binding sites for metals on microbial cell surfaces usually are carboxyl residues, phosphate residues, SH groups or hydroxyl groups; non-essential metals bind with greater affinity to the SH group (Srivastava et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The use of microbes to reduce, degrade or immobilize hazardous contaminants and clean up polluted environments results to be useful in bioremediation technology (Erdei et al 2005;Le Duc and Terry 2005;Benguella and Benaissa 2002;Saeed and Iqbal 2003;Deng et al 2007;Chen et al 2009), as demonstrated by metal bioremediation processes of industrial wastes (Srivastava et al 2008) and polluted effluents (Shukla et al 2009;Malekzadeh et al 2002) using bacteria such as Pseudomonas spp., Vallisneria spiralis, etc.…”
Section: Introductionmentioning
confidence: 98%
“…Microbiological removal of metal ions from the environment is a new biotechnique (Shukla et al 2009) and the most cost-effective approach in mitigation of elemental pollution. Heavy metals and their removal are well-researched issues as evident from the existing research literatures (Lovely and Coates 1997;Lovely and Lloyd 2000;Garbisu and Alkorta 2003;Malik 2004;Shukla and Rai 2006;Kabata-Pendias and Mukherjee 2007;Kim et al 2007;Srivastava et al 2008;Badri et al 2009;Rajkumar et al 2013) and the references therein. It is imperative to know that microbes in any case cannot degrade the metal ions and are only able to transform metallic ions from higher to lower oxidation states to stabilize them (Garbisu and Alkorta 2003).…”
Section: Microbial Remediation Of Inorganic Contaminantsmentioning
confidence: 99%